2009
DOI: 10.1211/jpp/61.04.0008
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between predicted and observed rates of intravenous gentamicin delivery for neonates

Abstract: The delivery of gentamicin administered by intravenous infusion is substantially extended in extremely low birth weight neonates. This appeared to be primarily due to the small volumes and low infusion rates used in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 18 publications
3
16
0
Order By: Relevance
“…Thus, in premature babies < 1 000 g, it was shown that only 70 % of the expected dose was delivered 75 min after the start of the drug infusion [7]. This is therefore problematic for certain drugs such as catecholamines, aminoglycosides or even insulin.…”
Section: Factorsmentioning
confidence: 99%
“…Thus, in premature babies < 1 000 g, it was shown that only 70 % of the expected dose was delivered 75 min after the start of the drug infusion [7]. This is therefore problematic for certain drugs such as catecholamines, aminoglycosides or even insulin.…”
Section: Factorsmentioning
confidence: 99%
“…Inconsistency of flow rate and drug passage through the intravenous line can present a challenge, with dead space in the line and components such as inline filters adding to the variability seen in intravenous delivery [54]. Sherwin et al demonstrated that gentamicin delivery may only reach 80 % of the expected delivery to normal-weight newborns after 60 min, while the reduced flow rates used for extremely-low-birthweight (0.5 kg) neonates may result in delivery of only 60 % of the expected drug dose in that time period [55]. Medlicott et al described other issues in intravenous delivery to neonates, including the potential for retrograde flow of the drug solution and poor mixing at the connection between the primary fluid and the drug solution resulting in delayed and/or incomplete gentamicin delivery [56].…”
Section: Intravenousmentioning
confidence: 99%
“…We have reported that this is not the case for one intravenous line configuration used in neonates where a marked discrepancy between the intended and administered gentamicin dose was seen, especially in low-birth-weight neonates. [7] We showed that less than 80% of the intended dose was delivered through the infusion line in 75 min when it was set up for administering a 30-min infusion in extremely low-birth-weight (ELBW, 500 g) neonates. [7] This may be overlooked in larger-population pharmacokinetic studies as the problem is expected to occur in only a small proportion of low-birth-weight pre-term neonates.…”
Section: Introductionmentioning
confidence: 99%
“…[7] We showed that less than 80% of the intended dose was delivered through the infusion line in 75 min when it was set up for administering a 30-min infusion in extremely low-birth-weight (ELBW, 500 g) neonates. [7] This may be overlooked in larger-population pharmacokinetic studies as the problem is expected to occur in only a small proportion of low-birth-weight pre-term neonates. Nahata has already reported that infusion set-ups affect tobramycin pharmacokinetic parameters (peak concentration, time to peak and volume of distribution).…”
Section: Introductionmentioning
confidence: 99%